Optimization of the surgical approach to treating hepatic cystic echinococcosis: A retrospective observational non-randomized study - V. S. Boyarinov; M. L. Rogal; S. V. Novikov; K. R. Dzhagraev; P. A. Yartsev (Кубанский научный медицинский вестник, 2024)
Background. Hepatic echinococcosis poses a great threat to human health and life. In order to minimize the risk of disability and speed up the postoperative recovery process, it is necessary to make an informed choice of the surgical treatment approach to be used. However, it is still unclear when traditional surgical methods should be applied and when less traumatic, minimally invasive, ultrasound-guided interventions can be used. This is what prompted this study. The article presents the results of using different surgical methods to treat patients with hepatic echinococcal cysts.Aim. To improve the outcomes of treating patients with hepatic cystic echinococcosis by optimizing the surgical approach using percutaneous minimally invasive and traditional surgical interventions.Methods. A non-randomized comparative study was conducted at the Sklifosovsky Institute for Emergency Medicine of the Moscow Department of Health. The subjects were treated in 2010–2020, with a follow-up period of four years after surgical treatment. A total of 78 patients with hepatic echinococcal cysts aged 18 to 78 years were treated. At the preoperative stage, medical history was collected from all patients, including data on migration during life. The diagnosis of all patients was confirmed through laboratory tests, instrumental methods (computed tomography and ultrasound), and a morphological examination of surgical material. All patients were divided into four groups: three groups of patients treated using different percutaneous minimally invasive methods and a comparison group of patients who underwent traditional surgery. The systematization of the material and its primary mathematical processing were performed using Excel 2016 (Microsoft, USA). The obtained numerical data were processed via methods of mathematical statistics using IBM SPSS Statistics 26 Version (IBM, USA).Results. In the sample distribution of the studied groups by gender, age, as well as the number of cysts and concomitant diseases, no statistically significant differences were identified; however, the study yielded several results indicating the advantages of using minimally invasive treatment for hepatic echinococcal cysts. In spite of the high likelihood of biliary fistulas and a suppurative residual cavity occurring with the use of minimally invasive methods, a statistically significant reduction in the operation time, duration of anesthesia in the postoperative period, and blood loss were observed, which in turn reduced the stay in the inpatient surgical facility.Conclusion. Minimally invasive methods can be used in all types of hepatic echinococcal cysts, as well as traditional surgery. It is reasonable to perform minimally invasive interventions if the clinic is adequately equipped and the surgeon is experienced in minimizing postoperative complications and recurrences.